PENGARUH CULTURE SHOCK TERHADAP KEHIDUPAN SOSIAL MAHASISWA RANTAU DI YOGYAKARTA - Yeni Febrianty; Ayu Romauli Octisa; Muhammad Arif Fuadi; Agung Dimas Dibrata; Muhamad Nastain (CV. ITTC INDONESIA, 2022)
The combination of students from various cultural backgrounds in one place is not a new phenomenon in Indonesia. When in a new place, overseas students will experience difficulties in studying, difficulty sleeping, feeling homesick, and having a decreased appetite. Thus, this study aims to determine the effect of culture shock on the social life of overseas students. The population in this study were students of the Faculty of Communication & Multimedia, Mercu Buana University Yogyakarta Class of 2021, while the sample was overseas students. This type of research is quantitative research. The instruments used in this study were culture shock questionnaires and student social life. The data obtained were then analyzed using SPSS software. The results of the study show that culture shock has a relationship with the social life of students, where a Pearson Correlation value of 0.541 is obtained, which means that there is a fairly strong relationship between the variable culture shock and the social life of students. In addition, it was also shown that culture shock affected the social life of overseas students by 29.2%. So that the other 71.8% is influenced by other variables not examined.